Genetic and Biochemical Characterization of Salmonella enterica Serovar Typhi Deoxyribokinase - Tourneux, Lise (American Society for Microbiology, 2000)
We identified in the genome of Salmonella enterica serovar Typhi the gene encoding deoxyribokinase, deoK. Two other genes, vicinal to deoK, were determined to encode the putative deoxyribose transporter (deoP) and a repressor protein (deoQ). This locus, located between the uhpA and ilvN genes, is absent in Escherichia coli. The deoK gene inserted on a plasmid provides a selectable marker in E. coli for growth on deoxyribose-containing medium. Deoxyribokinase is a 306-amino-acid protein which exhibits about 35% identity with ribokinase from serovar Typhi, S. enterica serovar Typhimurium, or E. coli. The catalytic properties of the recombinant deoxyribokinase overproduced in E. coli correspond to those previously described for the enzyme isolated from serovar Typhimurium. From a sequence comparison between serovar Typhi deoxyribokinase and E. coli ribokinase, whose crystal structure was recently solved, we deduced that a key residue differentiating ribose and deoxyribose is Met10, which in ribokinase is replaced by Asn14. Replacement by site-directed mutagenesis of Met10 with Asn decreased the V(max) of deoxyribokinase by a factor of 2.5 and increased the K(m) for deoxyribose by a factor of 70, compared to the parent enzyme.